Effect of room temperature on the quality of dna from earphone swab by observing mitochondrial dna [mtdna] D-loop region of 126 bp (hvs ii, nt 34-159) and 143 bp (hvs I, nt 16268-16410) - Yudianto, Ahmad; Margaret, Nola (Folia Medica Indonesiana, 2017)
The objects contained in crime scene and its surroundings have significance in the examination of forensic identification. The most commonly used specimens in the examination for identification are blood/blood spots, semen patches, vaginal swabs, buccal swabs and bones, including items often used by the perpetrator/victim the last time. For example, a mobile phone hearing aid (headset/earphone). In the use of earphones attached to the outer ear skin so it is suspected there is a serumen attached to the tool. One factor that can affect the quality of DNA is the prolonged exposure. Until now in Indonesia the effect of long exposure to room temperature on the quality of DNA on the DNA material of earphone swabs through DNA analysis has not been widely known. The type of study was laboratory experimental. Used earphones are exposed at room temperature within 1, 7, 14 and 20 days. The results of this study indicate that the environmental effect, ie the duration of exposure, affects the decrease in DNA content significantly from day 1 to 20. Detection of PCR mtDNA D-Loop HVS I visualization results 143 bp nt: 16268 16410 shows positive detection results (+) Only at day 1 exposure to room temperature [4 sample/66,67%] and day 7 [3 sample/50%]. Visualization of PCR results mtDNA D-Loop HVS II 126bp nt: 34 -159 was performed on day 1 day room exposure [2 sample/33,37%] and day 7 [6 sample/100%]. Conclusion, the duration of exposure to room temperature affect the quality of DNA from earpiece swab material. Decreased levels of earphones DNA swabs showed a significance value (p <0.005) against the effect of long time exposure to room temperature.